2012
DOI: 10.3109/01913123.2011.630125
|View full text |Cite
|
Sign up to set email alerts
|

Iron-induced Damage in Corpus Striatal Cells of Neonatal Rats: Attenuation by Folic Acid

Abstract: Intake of folic acid can protect the neonatal striatal tissue against iron-induced oxidative stress damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…In this regard, it was interesting to observe a relationship between higher transferrin saturation and increased CD8 + T-cell apoptosis. Iron induced apoptosis had been already reported in human hepatocytes and rat neurons but it had never been described in human lymphocytes [ 37 , 38 ]. It could be speculated that in this way iron overload could contribute to the decreased numbers of CD8 + T cells in HH.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it was interesting to observe a relationship between higher transferrin saturation and increased CD8 + T-cell apoptosis. Iron induced apoptosis had been already reported in human hepatocytes and rat neurons but it had never been described in human lymphocytes [ 37 , 38 ]. It could be speculated that in this way iron overload could contribute to the decreased numbers of CD8 + T cells in HH.…”
Section: Discussionmentioning
confidence: 99%
“…Although the underlying mechanism of this therapy is not completely understood (Copp et al, 2013). We hypothesized a possible connection between folic acid supplementation and HO-1 based on the work of Saadeldien and others, who demonstrated that folic acid reduced oxidative damage from iron supplementation in neonatal rodent neuronal tissues (Saadeldien et al, 2012). Since we did not have data on folic acid supplementation in early pregnancy, the additional hypothesis about a modifying influence between folate and HO-1 variants could not be tested.…”
Section: Discussionmentioning
confidence: 99%
“…GFAP staining was also slightly reduced in FA-treated pregnant rats. Saadeldien et al 49 found that maternal FA intake reduced iron-induced oxidative stress damage and GFAP expression levels in striatal tissue. Accordingly, we also observed decreased cortical GFAP expression in seizure-induced prepubertal rats born to FA-treated mothers ( Fig.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%